Una aproximación teórica a la obra de Arturo Valencia Zea De la posesión y la función social de la propiedad: el gran problema jurídico del siglo xx en Colombia, revisión histórico jurídica (2018)
The present manuscript aims to contextualize the notion of possession and ownership from a qualitative research methodology and in accordance with historical-juridical research method. For the purposes of the above, the analysis is based on the doctrine proposed by Professor Arturo Valencia Zea, who analyzes the European Doctrine, to analyze the legal nature of the referenced legal institutions, aspects that are intended to be described in this manuscript.